El tipo subjetivo en los delitos de tentativa de asesinato y robo con resultado de lesiones - Ramírez Blacio, María Andrea (2018)
In the present work of titillation, we face the case of concrete study of the Case of BOLIVAR ANDRES VALDIVIEZO NEIRA, of the crime of ASSASSINATION in the degree of attempt, the same that was sanctioned by supposedly to have infringed the norm contained in the criminal law that prohibits attempt against the lives of people, since it is a protected legal asset. The central objective of the investigation was to determine whether the conviction of Bolivar Andres Valdiviezo Neira was legitimate, that is, the offense was actually demonstrated both objectively and subjectively; for this, a qualitative research was carried out, where the discussions of the bibliographic contents with which the theoretical framework of the research was developed were decisive. The object of study is therefore the Subjective Type in the crimes of Attempt of Assassination and Theft resulting in injuries, fundamental rights that have come into conflict in the criminal setting.